Incalculating halal values in seaweed production for competitive positioning - Mohammad Noor, Normawaty; Muhammad Noor, Sarina; Anwar, Encik Weliyadi; Saleh, Rukisah (2016)
Seaweed industry is important in several countries including Malaysia, Japan, Indonesia, and the Philippines. The seaweed, Kappaphycus is widely used in variety of food products as an excellent nutritional supplement. There are several stages in producing raw Kappaphycus for industry such as cultivation and harvest. Meanwhile, Halal is a concept that stress on shariah law and utmost quality. However, the knowledge of halal is still limited in marine production including seaweed. Currently the seaweed process has gone through numerous stages yet none of them has been checked on it Halalness aspect. This paper intends to deliberate on the aspect of Halalness for each stages involved in cultivation and harvest. Through observations and literature search, findings showed that there is lack of hygienic practices in handling seaweed production. In this paper, few recommendations were suggested to enhance the value proposition of the seaweed production as it complies with the concept of halalness. This will contribute towards the development of halal ecosystem from seed to harvest of quality seaweed production